2017
DOI: 10.1111/and.12872
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of the ratio of serum total testosterone to total prostate-specific antigen in the diagnosis of prostate cancer in a Chinese population

Abstract: We investigated whether serum testosterone and testosterone/prostate-specific antigen ratio (T/PSA) might be prostate cancer (PCa) biomarkers. We retrospectively reviewed 92 patients with benign prostatic hyperplasia (BPH) and 164 patients with PCa treated at Zhongshan Hospital, China (April 2012 to November 2013). The BPH and PCa groups had similar serum total testosterone (median, 15.8 versus 16.3 nmol/L).Compared with the BPH group, the PCa group had higher PSA (16.8 versus 5.1 ng/ml) and lower free/total P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Postoperative PSA changes in BPH patients have also been reported, but mainly in TURP studies, and HoLEP studies remain few in comparison. The findings in our study are aligned with previous studies in that elevated PSA levels showed correlations with AUR, BOO, and prostate volume [11]. Patients with larger prostates have been reported in the literature to show higher PSA levels before HoLEP and had a significantly greater decrease after surgery [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Postoperative PSA changes in BPH patients have also been reported, but mainly in TURP studies, and HoLEP studies remain few in comparison. The findings in our study are aligned with previous studies in that elevated PSA levels showed correlations with AUR, BOO, and prostate volume [11]. Patients with larger prostates have been reported in the literature to show higher PSA levels before HoLEP and had a significantly greater decrease after surgery [21].…”
Section: Discussionsupporting
confidence: 92%
“…P-Bx was considered when the PSA level was high ( ≥3.0 ng/mL), when a digital rectal exam showed suspicious findings, and/or when imaging showed abnormal findings [10]. For patients taking 5-alpha reductase inhibitors (5-ARIs), the PSA value was multiplied by 2 [11], and this doubled value was used to determine whether to perform a P-Bx. At our institution, until 2017, 12-core biopsies were conducted near the base, midgland, and apex.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate cancer detection accuracy has been improved with the use of the PSA/testosterone ratio (Gurbuz et al 2012, Xu et al 2018. In contrast, adjusting only for obesity in addition to PSA did not improve specificity (Oh et al 2013, Banez et al 2014, Vidal et al 2015, Harrison et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different from our results, Xu et al compared 92 patients with BPH and 164 patients with PCa from the Chinese population in their study and reported lower TT/tPSA ratios in the PCa group compared to the BPH group. 13 However, they reported that serum TT levels were similar in those 2 groups. Rhoden et al reported a 3-fold increased risk of PCa in patients with a TT/tPSA ratio of less than 1.8.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, several studies with different outcomes investigated the predictive role of serum testosterone levels and the serum total testosterone (TT)/total PSA (tPSA) ratio on PCa through different methodologies in this population. [9][10][11][12][13][14][15][16] In this study, we have aimed to investigate the adjunctive role of some hematological and biochemical parameters in patients with gray-zone serum PSA levels (2.5-10 ng/mL) for making the differential diagnosis between benign and malignant diseases of the prostate gland prior to prostate biopsy. Furthermore, we have aimed to examine the role of such parameters in predicting the clinically significant PCa grouped according to Epstein criteria.…”
mentioning
confidence: 99%